Reflexive Impersonal Constructions Expressing an Arbitrary Agent in Slovenian - Uhlik, Mladen; Žele, Andreja (Slavistica Vilnensis, 2020)
The article presents formal, semantic, and pragmatic features of Slovenian subject impersonal reflexive constructions, e. g. Nekoč se je veliko delalo ‘Back in the day, one used to work a lot’. Constructions with unexpressed arbitrary agents should be distinguished from sentences in which the nominative agent has been omitted, but can be determined from the context. Subject impersonal reflexive constructions use the reflexive forms of non-reflexive verbs. In such constructions, the morpheme se is a grammaticalized element that does not express a reflexive action. The constructions under discussion can express habitual or iterative actions performed by a non-expressed human agent and can also have a deontic meaning. Reflexive constructions with arbitrary agents mainly involve verbs denoting conscious human actions and activities, which sets them apart from weather impersonals or subjectless constructions describing physiological states. Subject impersonals, characteristic of South Slavic and West Slavic languages, are parallel to those in which the arbitrary agent is expressed lexically (Nekoč so ljudje veliko delali ‘Back in the day, people used to work a lot’). We compare subject impersonals with other impersonal and passive constructions in Slovenian and, at the same time, contrast their features with similar constructions in other South Slavic languages and Russian.
Keywords: subject impersonals; reflexive constructions; impersonal constructions; arbitrary agent; Slovenian; South Slavic languages